Isolation and quantification of indicator and pathogenic microorganisms along with their drug resistance traits from bottled and jar water samples within Dhaka city, Bangladesh - Uddin, Md Aftab; Siddiqua, Mst Aysha; Ahmed, Mst Sadia (Stamford Journal of Microbiology, 2020)
Commercial drinking water may serve as potential threat to public health if these items are contaminated with a number of pathogenic microorganisms due to faulty manufacturing process. Present study attempted to isolate and quantify the microorganisms from various jar and bottle water samples collected from various areas of Dhaka city. Antibiotic susceptibility pattern of suspected bacterial isolates were also determined in this study. Out of the eighteen samples studied, ten were jar water samples and eight were bottled water samples. The range of total viable bacterial count (TVBC) in these samples ranged from 102 to 105 cfu/ml. Specific pathogens such as, Salmonella spp., Shigella spp., Vibrio spp. and fecal coliforms could not be found in these samples. However coliforms could be detected in 10 samples. The antibiogram study showed that all Escherichia coli and Klebsiella spp. isolates found from these samples were sensitive against gentamicin (10 μg) and azithromycin (30 μg). Variable antibiotic resistance among these bacterial isolates was detected against cefotaxime (30 μg), streptomycin (10 μg) and erythromycin (15 μg). Stamford Journal of Microbiology, Vol.9(1) 2019: 12-14